A response to Aili Tripp. (2nd April 2016) - Yuval-Davis, Nira
Abstract : In this response which is generally sympathetic and agrees with many of Aili Tripp's points, I raise a couple of issues which divert or are somewhat different from hers. For example, unlike the way in which Tripp's essay emphasizes geographical/cultural differences as a comparative framework, I propose that it is the political aim of the particular feminist activism that acts as the primary reason why certain feminist political projects emphasize similarity and others differences among women. I also discuss in this respect transversal politics, in which women (and other groupings) cooperate across borders and boundaries, recognizing their different social locations and identifications, but sharing their common feminist and emancipatory political perspectives, working through a dialogical epistemology. In transversal politics the activists, however, should not see themselves as representing all women or even all women from their collectivity but rather as their advocates. When this is not the case, there is a danger of essentialist construction of womanhood and gender roles. This is why measures, like the UN 1325 resolution that calls for the increase of the number of women as 'women' participants in peace negotiations to be mandatory, can be a double- edge sword, as not all women should be seen as promoters of peace.